Study about the Relationship between Accounting and Taxation. Proposals for Disconnection - MARIANA GURĂU; MARIA ZENOVIA GRIGORE (Global Economic Observer)
The observation that many practitioners, by virtue of strong dependence between accounting and taxation encountered in our country after years of "90, find with difficulty the way to detachment of accounting and taxation by making cautious steps, lack of courage, was the impulse for choosing this research topic. Therefore, we consider that research in accounting and taxation field must represent the combination of information obtained as a result of theoretical research with information from economic reality. By its content, this study, perform extensive research on the intersection of accounting information with tax elements, combination oriented to disconnection between the two areas.